2013
DOI: 10.1089/scd.2012.0202
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Differentiation and Maturation of Human Embryonic Stem Cells Cultured in a Perfused Three-Dimensional Bioreactor

Abstract: Drug-induced liver injury is a serious and frequently occurring adverse drug reaction in the clinics and is hard to predict during preclinical studies. Today, primary hepatocytes are the most frequently used cell model for drug discovery and prediction of toxicity. However, their use is marred by high donor variability regarding drug metabolism and toxicity, and instable expression levels of liver-specific genes such as cytochromes P450. An in vitro model system based on human embryonic stem cells (hESC), with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 47 publications
2
35
0
Order By: Relevance
“…The first is the generation of 3D aggregates. As shown in previous studies (Miki et al, 2011;Sivertsson et al, 2013) and in the work reported here, culture of hPSC-derived hepatic cells as 3D aggregates leads to the upregulation of expression of a wide range of genes involved in different aspects of liver function. Aggregation alone, however, does not appear to promote maturation of the population to the stage at which the cells have functional levels of enzyme activity.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The first is the generation of 3D aggregates. As shown in previous studies (Miki et al, 2011;Sivertsson et al, 2013) and in the work reported here, culture of hPSC-derived hepatic cells as 3D aggregates leads to the upregulation of expression of a wide range of genes involved in different aspects of liver function. Aggregation alone, however, does not appear to promote maturation of the population to the stage at which the cells have functional levels of enzyme activity.…”
Section: Discussionsupporting
confidence: 84%
“…This study did not, however, provide any insights into the pathways that promote maturation or show that the approach was applicable to different cell lines. More recent studies have shown that culture on specific polymers (Hay et al, 2011), culture as 3D aggregates (Sivertsson et al, 2013) or the combination of enforced expression of key transcription factors together with 3D aggregation (Takayama et al, 2013) promote the development hPSC-derived hepatocytes that express CYP genes. Of these, only two showed inducible CYP activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, in these hollow-fibre bioreactors, the differentiation of human embryonic stem cells towards hepatic cells as a potential alternative cell source for studies on hepatic cells is demonstrated by a significant up-regulation of genes related to liver functions (Miki et al, 2011) and enhanced hepatic differentiation in the 3D four-compartment bioreactor system compared to conventional 2D cultures (Sivertsson et al, 2013).…”
Section: Limitations Of 3d Organotypic Liver Modelsmentioning
confidence: 99%
“…The properties of hESC (capacity to differentiate to all major cell types) are also found in other human pluripotent stem cells, such as human induced pluripotent stem cells (hiPSC) or cells generated by nuclear transfer 5 . For instance, many different hESC lines have been differentiated into neurons 6 , renal cells 7 , neural crest cells 8 , cardiomyocytes [9][10][11][12] , or hepatocytes like cells 13,14 . Moreover, hESC can spontaneously differentiate into cells of all three germ layers [15][16][17][18] in embryoid bodies (EBs) specific signatures have been captured by transcriptomics profile using the Affymetrix microarray platform.…”
Section: Introductionmentioning
confidence: 99%